HIP fracture Supplemental Therapy to Enhance Recovery (HIPSTER): a protocol for a randomised controlled trial - Belinda J Gabbe; Ian A Harris; Graham Hepworth; Richard Page; Ilana N Ackerman; Anthony Harris; Anne E Holland; Justine M Naylor; Christina L Ekegren; Angela T Burge; Maame Esi Woode; Eleanor Raper; et al. (BMJ Open)
Introduction Hip fractures result in substantial health impacts for patients and costs to health systems. Many patients require prolonged hospital stays and up to 60% do not regain their prefracture level of mobility within 1 year. Physical rehabilitation plays a key role in regaining physical function and independence; however, there are no recommendations regarding the optimal intensity. This study aims to compare the clinical efficacy and cost-effectiveness of early intensive in-hospital physiotherapy compared with usual care in patients who have had surgery following a hip fracture.Methods and analysis This two-arm randomised, controlled, assessor-blinded trial will recruit 620 participants who have had surgery following a hip fracture from eight hospitals. Participants will be randomised 1:1 to receive usual care (physiotherapy according to usual practice at the site) or intensive physiotherapy in the hospital over the first 7 days following surgery (two additional sessions per day, one delivered by a physiotherapist and the other by an allied health assistant). The primary outcome is the total hospital length of stay, measured from the date of hospital admission to the date of hospital discharge, including both acute and subacute hospital days. Secondary outcomes are functional mobility, health-related quality of life, concerns about falling, discharge destination, proportion of patients remaining in hospital at 30 days, return to preadmission mobility and residence at 120 days and adverse events. Twelve months of follow-up will capture data on healthcare utilisation. A cost-effectiveness evaluation will be undertaken, and a process evaluation will document barriers and facilitators to implementation.Ethics and dissemination The Alfred Hospital Ethics Committee has approved this protocol. The trial findings will be published in peer-reviewed journals, submitted for presentation at conferences and disseminated to patients and carers.Trial registration number ACTRN12622001442796.